OP10 Relaxin inhibits human myofibroblast contractility and modulates portal hypertension in vivo. (16th November 2010) - Fallowfield, J; Hayden, A; Aucott, R; Schrader, J; Gordon-Walker, T; Mole, D; Collins, J; Iredale, J
Abstract : Introduction: The peptide hormone relaxin (H2-RLN) has a broad range of biological activities including antifibrotic, anti-inflammatory and haemodynamic effects in a range of target tissues. Increased intrahepatic vascular resistance in cirrhosis is due to mechanical factors related to scarring, but also a dynamic component mediated by myofibroblast (MFB) contractility. We hypothesised that H2-RLN could modulate the dynamic attribute of portal hypertension (PHT) via a direct effect on hepatic stellate cell (HSC)-MFB mediated vasoconstriction. Aim: To determine whether H2-RLN could target the contractile phenotype of activated HSC-MFBs in vitro, counterbalance the contractile response in vivo in a model of sinusoidal portal hypertension, and explore the mechanisms underlying its portal hypotensive effect. Method: Gene expression in culture activated human HSCs was analysed by qRT-PCR and Western blotting. Collagen gel contraction assays were used to assess HSC-MFB contractility. Nitric oxide (NO) production was measured by Griess assay. Cirrhosis and portal hypertension was induced in age matched male Sprague–Dawley rats by 8 weeks bi-weekly i.p. CCl4, before randomisation to treatment with recombinant human H2-RLN or placebo delivered by s.c. osmotic minipump for 72 hrs (n=10 per group). Portal pressure was measured by direct cannulation. Serum H2-RLN levels were quantified by immunoassay. Liver fibrosis was measured after Sirius red staining by calculation of collagen proportionate area by digital image analysis. Finally, systemic arterial and portal pressure was measured simultaneously in groups of cirrhotic and control rats randomised to acute i.v. H2-RLN or placebo. Results: Treatment of culture activated HSCs with H2-RLN downregulated expression of the major cytoskeletal protein, alpha-smooth muscle actin (alpha-SMA), in a dose dependent manner. In collagen gel contraction assays, H2-RLN inhibited HSC-MFB contraction, an effect shown by RNA interference to be mediated via RXFP-1 receptor signaling and increased NO production. Rats treated with CCl4 for 8 weeks developed micronodular cirrhosis, splenomegaly and portal hypertension. Treatment with s.c. H2-RLN for 72 h achieved physiologically relevant serum concentrations and decreased portal pressure by 24% (mean 12.8±0.8 mm Hg vs 9.8±0.3 mm Hg; p=0.002), whereas placebo had no significant effect. The observed haemodynamic response was independent of fibrosis regression. Hepatic expression of alpha-SMA and other intermediate filament proteins was markedly inhibited by H2-RLN, while eNOS activity was increased. Infusion of i.v. H2-RLN in cirrhotic rats rapidly depressed portal pressure (mean 28%±6) but not systemic pressure, compared to placebo which had minimal effect on either parameter. Conclusion: We demonstrate for the first time that H2-RLN will effectively downregulate MFB contractile filament expression, contractile function and has a portal hypotensive effect in vivo. Our findings support the deployment of H2-RLN in clinical studies of cirrhosis and PHT.